2016
DOI: 10.1002/ange.201510064
|View full text |Cite
|
Sign up to set email alerts
|

Remote‐Controlled Release of Singlet Oxygen by the Plasmonic Heating of Endoperoxide‐Modified Gold Nanorods: Towards a Paradigm Change in Photodynamic Therapy

Abstract: The photodynamic therapyo fc ancer is contingent upon the sustained generation of singlet oxygen in the tumor region. However,t umors of the most metastatic cancer types develop ar egion of severe hypoxia, whichp uts them beyond the reach of most therapeutic protocols.M ore troublesome, photodynamic action generates acute hypoxia as the process itself diminishes cellular oxygen reserves,whichmakes it aselflimiting method. Herein, we describe anew concept that could eventually lead to ac hange in the 100 year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 31 publications
(23 reference statements)
0
37
0
Order By: Relevance
“…14 Kolemen et al reported another system with the potential to solve the hypoxia limitation of PDT. 15 The authors used non-conventional chemical photosensitisers, endoperoxides of arenes, which lead to the production of 1 O2 upon heating via controlled cycloreversion.…”
Section: The Use Of Thiolated Peg and Other Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Kolemen et al reported another system with the potential to solve the hypoxia limitation of PDT. 15 The authors used non-conventional chemical photosensitisers, endoperoxides of arenes, which lead to the production of 1 O2 upon heating via controlled cycloreversion.…”
Section: The Use Of Thiolated Peg and Other Polymersmentioning
confidence: 99%
“…A further advantage of the use of endoperoxides as photosensitisers is their irradiation with NIR light, which can penetrate deeper than commonly used red light into biological tissue, thus opening the possibility to treat deep-lying tumours. 15 In a further attempt to increase light penetration into the tissue, Clement et al…”
Section: The Use Of Thiolated Peg and Other Polymersmentioning
confidence: 99%
“…The singlet oxygen ( 1 O 2 )g eneration efficiency of photosensitizers is an important factor in PDT. [35,36] AN IR laser and aL ED light were used as the light sourcesi nt his study because of their tissue penetration properties and safety toward the cells. To confirm the photodynamic activity of GO-HNP-PpIX, 1 O 2 generation was detected by ac hemical trappingm ethodw ith 9,10-anthracenediyl bis(methylene)dimalonic acid (ABDA).…”
Section: Resultsmentioning
confidence: 99%
“…As a promising alternative or supplement to traditional cancer therapy, PTT is minimally invasive and compensates for the reduced therapeutic efficacy caused by chemodrug resistance. In addition, PTT can be combined with other therapeutic methodologies, such as chemotherapy and gene therapy, to achieve high therapeutic efficacy against cancer [15][16][17] . Nevertheless, recent studies have indicated that PTT is always accompanied by a heat shock response that shields cancer cells from damage by hyperthermia, decreasing its therapeutic efficacy [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%